Marketing Management Strategy in Increasing Sales of Aluminum and Glass Products at the Mustika Jaya Store in Ciampea District, Bogor Regency - Pramuja, Do'ang (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The focus of this research is aimed at describing aluminum and glass marketing management strategies in aspects of increasing product sales at Mustika Jaya Aluminum Store in Ciampea District, Bogor Regency. This research uses qualitative methods by conducting in-depth interviews with business owners in collecting research data. The results showed that the marketing management strategy in increasing sales of aluminum products at Toko Mustika Jaya Aluminum in Ciampea District, Bogor Regency is to use the 4P marketing mix strategy (price, place, product, and promotion) with targets generally selling groceries, itinerant sellers, housewives, building contractors or projects, as well as aluminum and glass shops. Distribution and market access carried out by Toko Mustika Jaya Aluminum in Ciampea District, Bogor Regency is by the waterfall method which runs through the Website with the 4M principle, namely offering, marketing, shaping, and implementing.